2003
DOI: 10.1074/jbc.m308674200
|View full text |Cite
|
Sign up to set email alerts
|

Yeast β-Alanine Synthase Shares a Structural Scaffold and Origin with Dizinc-dependent Exopeptidases

Abstract: ␤-Alanine synthase (␤AS) is the final enzyme of the reductive pyrimidine catabolic pathway, which is responsible for the breakdown of pyrimidine bases, including several anticancer drugs. In eukaryotes, ␤ASs belong to two subfamilies, which exhibit a low degree of sequence similarity. We determined the structure of ␤AS from Saccharomyces kluyveri to a resolution of 2.7 Å. The subunit of the homodimeric enzyme consists of two domains: a larger catalytic domain with a dizinc metal center, which represents the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 38 publications
(28 reference statements)
0
67
0
Order By: Relevance
“…4). It is not clear if ureidopropionate is converted to ␤-alanine by spontaneous hydrolysis (8) or if the identification of the S. pombe ␤-alanine synthase is prevented by the sequence diversity known to occur in eukaryotic ␤-alanine synthases (16,24).…”
Section: Discussionmentioning
confidence: 99%
“…4). It is not clear if ureidopropionate is converted to ␤-alanine by spontaneous hydrolysis (8) or if the identification of the S. pombe ␤-alanine synthase is prevented by the sequence diversity known to occur in eukaryotic ␤-alanine synthases (16,24).…”
Section: Discussionmentioning
confidence: 99%
“…Among the five residues involved in the binuclear metal center in the structures known to date (Table 2), the M2 binding residues (BsLcar Glu 125 and His 380 ) are totally conserved, whereas M1 binding residues present a higher level of divergence (His 79 is also fully conserved, but His 189 may appear as a Glu or Asp residue). This divergence was explained for the homologous EcAam and Sk␤as enzymes, as a His residue would allow a lower pK a of the Zn-bound water than that with a negatively charged lateral chain (Glu or Asp) (2,38). In fact, the His residue would allow an increased nucleophilicity of the attacking hydroxyl, which was hypothesized as necessary to hydrolyze a carbamoyl moiety compared to a peptide bond due to the better resonance stabilization of the ureido group (2,38).…”
Section: R369 H219(a) N260(a)mentioning
confidence: 99%
“…This divergence was explained for the homologous EcAam and Sk␤as enzymes, as a His residue would allow a lower pK a of the Zn-bound water than that with a negatively charged lateral chain (Glu or Asp) (2,38). In fact, the His residue would allow an increased nucleophilicity of the attacking hydroxyl, which was hypothesized as necessary to hydrolyze a carbamoyl moiety compared to a peptide bond due to the better resonance stabilization of the ureido group (2,38). Although the same hypothesis would support a BsLcar mechanism dependent on a single cation (as M1 is coordinated through two His residues, like the case for EcAam and Sk␤as) ( Table 2; see Fig.…”
Section: R369 H219(a) N260(a)mentioning
confidence: 99%
See 1 more Smart Citation
“…Phylogenetic analyses revealed that they can be assigned to two subfamilies (Gojković et al, 2001), with the majority of the eukaryotic enzymes, including those from human, calf, rat and fruit fly, forming one of them. The enzyme from the yeast Saccharomyces kluyveri, to date the only AS with known crystal structure Lundgren et al, 2003), shows no sequence similarity to this group but is related to bacterial N-carbamyl-l-amino-acid amidohydrolases, hence forming a separate subfamily. It is a dimer of identical subunits comprising two domains with / topology, the larger of which contains a di-zinc centre that is essential for catalytic activity.…”
Section: Introductionmentioning
confidence: 99%